رؤیت ہلال کے فیصلہ میں فلکی حسابات کے اعتبار و عدم اعتبار کا مسئلہ - محمد مشتاق احمد (FIKR-O NAZAR فکر ونظر, 2010)
The paper argues that Islamic law has prescribed two criteria for th beginning of the lunar months: one, is sighting of the crescent on the 29th day of the lunar month; and second, completion of 30 days when the moon is not sighted. The beginning of the new Islamic month cannot be decided merely on the basis of the predictions of the astronomers and scientists about the "birth of new moon" or conjunction. This is because the beginning of Islamic month on the basis of the calculation and predictions of scientists violates some fundamental norms of Islamic law, which have been explicitly laid down in the texts of the Qur’an and the Sunnah. These fundamental norms of Islamic law cannot be suspended on the basis of some presumed public interest. For beginning of an Islamic month, the law makes it obligatory that testimony (shahadah) of the sighting of the moon is accepted by the ruler or any person or persons authorized by him in this regard. However, the opinion of scientists based on scientific calculations and definitive evidences has the same status as that of the "expert opinion" under the law of evidence and as such the testimony of witnesses about moonsighting can be rejected if it is against the definitive expert opinion.